A Review of Recent Advances in Upper Extremity Orthoses for Rehabilitation Therapy and Improved Functional Independence - H. Hoffman, Allen (Recent Patents on Biomedical Engineering (Discontinued), 2012)
Orthoses are a form of exoskeleton that attach to a limb or to the torso. Upper extremity orthoses have been developed in response to two distinct needs; improved rehabilitation therapy and devices that aid persons with disabilities in performing activities of daily living. In the past, therapists have provided therapy to those affected by conditions such as stroke by repetitive manipulation of the affected body segments. Several types of upper extremity orthoses have been developed which enable the therapist to increase the dosage and intensity of therapy. Orthoses have also been developed for persons with more permanent disabling conditions to improve their functional independence. These devices focus on enabling specific tasks that are usually associated the workplace or daily living. This article primarily reviews patents related to powered upper extremity orthoses used in rehabilitation or as assistive devices and their current applications. Concluding remarks explore possible future developments in both of these areas.
Keywords: disabilities